2005
DOI: 10.1179/oeh.2005.11.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the Italian Studies of Short-term Effects of Air Pollution (MISA), 1990–1999

Abstract: A meta-analysis of short-term effects of air pollution on health in eight Italian cities from 1990 to 1999 is presented. Death certificates and hospital admission data as well as daily concentrations of pollutants were collected. The same generalized linear model adjusted for age, day of the week, holidays, influenza epidemics, meteorological variables, and seasonality pattern was fitted to the city data. City-specific model selection was not done. In the meta-analysis, for each outcome, the city-specific esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 17 publications
10
90
2
4
Order By: Relevance
“…Previous study showed that an increase of 10 μg/m 3 in SO 2 was associated with an increase of 2.4 % in hospital admissions respiratory cases in six Italian cities (Biggeri et al 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Previous study showed that an increase of 10 μg/m 3 in SO 2 was associated with an increase of 2.4 % in hospital admissions respiratory cases in six Italian cities (Biggeri et al 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Typically, short-term mortality rates, hospital admissions and emergency room visits for exacerbations of existing symptoms did increase in relation to variations in air pollution (time-series studies). A recent update of the Meta-analysis of Italian Studies on the short-term effects of Air pollution [21], that considered data on 9 million people from 15 Italian cities for the period 1996-2002, showed that cardiorespiratory mortality increased with increasing concentrations of air pollutants (for NO 2 0.40%, for CO 0.93%, for SO 2 1.11% and for PM 10 0.54%). Similar results were obtained in studies carried out in French and Spanish urban areas [22][23][24].…”
Section: Effects On Mortalitymentioning
confidence: 99%
“…La asociación del material particulado con la salud ha sido ampliamente estudiada en las ciudades europeas, norteamericanas y asiáticas [17][18][19][20][21][22][23][24][25] . En general, los resultados de estos estudios son consistentes en el sentido de que la gran mayoría de ellos encuentran una asociación significativa en el corto plazo (es decir, entre el mismo día de la exposición y unos pocos días después) con los indicadores de mortalidad y morbilidad.…”
Section: Discussionunclassified